Late Outcomes of the RAPID-TnT Randomized Controlled Trial: 0/1-Hour High-Sensitivity Troponin T Protocol in Suspected ACS. Issue 2 (13th July 2021) - Lambrakis, Kristina; Papendick, Cynthia; French, John K.; Quinn, Stephen; Blyth, Andrew; Seshadri, Anil; Edmonds, Michael J.R.; Chuang, Anthony; Khan, Ehsan; Nelson, Adam J.; Wright, Deborah; Horsfall, Matthew; et al.
Abstract : Background: High-sensitivity troponin assays are increasingly being adopted to expedite evaluation of patients with suspected acute coronary syndromes. Few direct comparisons have examined whether the enhanced performance of these assays at low concentrations leads to changes in care that improves longer-term outcomes. This study evaluated late outcomes of participants managed under an unmasked 0/1-hour high-sensitivity cardiac troponin T (hs-cTnT) protocol compared with a 0/3-hour masked hs-cTnT protocol. Methods: We conducted a multicenter prospective patient-level randomized comparison of care informed by unmasked 0/1-hour hs-cTnT protocol (reported to <5 ng/L) versus standard practice masked hs-cTnT testing (reported to ⩽29 ng/L) assessed at 0/3 hours and followed participants for 12 months. Participants included were those presenting to metropolitan emergency departments with suspected acute coronary syndromes, without ECG evidence of coronary ischemia. The primary end point was time to all-cause death or myocardial infarction using Cox proportional hazards models adjusted for clustering within hospitals. Results: Between August 2015 and April 2019, we randomized 3378 participants, of whom 108 withdrew, resulting in 12-month follow-up for 3270 participants (masked: 1632; unmasked: 1638). Among these, 2993 (91.5%) had an initial troponin concentration of ⩽29 ng/L. Deployment of the 0/1-hour hs-cTnT protocol was associated with reductions in functional testing. Over 12-month follow-up, there was no difference in invasive coronary angiography (0/1-hour unmasked: 232/1638 [14.2%]; 0/3-hour masked: 202/1632 [12.4%]; P =0.13), although an increase was seen among patients with hs-cTnT levels within the masked range (0/1-hour unmasked arm: 168/1507 [11.2%]; 0/3-hour masked arm: 124/1486 [8.3%]; P =0.010). By 12 months, all-cause death and myocardial infarction did not differ between study arms overall (0/1-hour: 82/1638 [5.0%] versus 0/3-hour: 62/1632 [3.8%]; hazard ratio, 1.32 [95% CI, 0.95–1.83]; P =0.10). Among participants with initial troponin T concentrations ⩽29 ng/L, unmasked hs-cTnT reporting was associated with an increase in death or myocardial infarction (0/1-hour: 55/1507 [3.7%] versus 0/3-hour: 34/1486 [2.3%]; hazard ratio, 1.60 [95% CI, 1.05–2.46]; P =0.030). Conclusions: Unmasked hs-cTnT reporting deployed within a 0/1-hour protocol did not reduce ischemic events over 12-month follow-up. Changes in practice associated with the implementation of this protocol may be associated with an increase in death and myocardial infarction among those with newly identified troponin elevations. Registration: URL: https://www.anzctr.org.au ; Unique identifier: ACTRN12615001379505. Abstract : Supplemental Digital Content is available in the text.